Spanish adaptation and validation of the empowerment of parents in the intensive care-neonatology (EMPATHIC-N) questionnaire - Ruiz-González, C.; Martín-Casas, P.; Latour, Jos; Úbeda-Tikkanen, A.; López-de-Uralde-Villanueva, I.; Sánchez-Aparicio García, S.; Cuadrado-Obregón, N. (2023)
Introduction: Parental satisfaction is rarely measured in the neonatal intensive care unit due to a lack of specific assessment tools. The EMpowerment of PArents in THe Intensive Care-Neonatology (EMPATHIC-N) questionnaire is an instrument to assess satisfaction in relation to family-centred care that has been validated in several countries, but not Spain. Objectives: To perform the translation and cultural adaptation of the EMPATHIC-N to Spanish followed by its validation for the purpose of assessing satisfaction in parents with children admitted to the neonatal intensive care unit. Material and methods: The questionnaire first underwent forward and backward translation and transcultural adaptation by a panel of experts through a standardized process based on the Delphi method, followed by a pilot study in 8 parents and then a cross-sectional study in the neonatal intensive care unit of a tertiary care hospital to assess the reliability and converging validity of the Spanish version. Results: The study proved the comprehensibility, validity, feasibility, applicability and usefulness of the Spanish version of the EMPATHIC-N in the field of paediatric health after being evaluated by 19 professionals and 60 parents. The content validity was found to be excellent (0.93). The reliability and convergent validity of the Spanish version of the EMPHATIC-N was analysed in a sample of 65 completed questionnaires. The Cronbach α for each domain was greater than 0.7, indicating a high internal consistency. We assessed validity by analysing the correlation of the 5 domains with the with the 4 general satisfaction items. The validity was found to be adequate (rs, 0.4-0.76; P <.01). Conclusions: The Spanish version of the EMPATHIC-N questionnaire is a comprehensible, useful, valid and reliable instrument to measure satisfaction in the parents of children admitted to neonatal care units.